Implementasi Publish-Subscribe pada Delay Tolerant Network (DTN) - Rembulan Suci Fii Jannatin; Aswin Suharsono; Adhitya Bhawiyuga (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
In the rapid development of information technology, many efforts has been done to provide more efficient and effective service for information exchange. One of the architecture that attracts researchers's attention is publish-subscribe architecture, which included in Information Centric Networking (ICN). Publish-subscribe system will help data exchange between nodes. Subscriber node will not care who is the data sender as long as the data matched the topic they has subscribe. The current publish-subscribe application is not capable to run in area with unstable connection. One of the solutions to solve that problem is to build publish-subscribe architecture in Delay Tolerant Network (DTN). In this study, publisher had uploaded some book file. Brokers had been able to forward the files to subscriber according the topic. Subscriber had been able to receive files published by publisher according the topic they choose. Three of them run in DTN. Success rate of sending files to destination in testing of 5000 file-sending is 100%. All files had been sent successfully to broker and subscribers according to its destination without data-lost. File with size of 1 MB, more than 10 MB, and more than 100 MB had been successfully uploaded to publsiher's storage and also successfully sent to subscribers. This system also has re-sending mechanism for lost data-packets that functions properly.